Multimedia tutorial courseware on Jawi alphabets and numbers / Nor Fadhillah Abd Manap - Abd Manap, Nor Fadhillah (2005)
Multimedk tutorial courseware has become more important now^ays. This is due to its ability and interactivity to the user. Furthermore, it provides non-linear process of learning compared to traditional vray of teaching and learning. Other approach can be added to an application to make it more dynamic and interesting such as gaming approach to attract the children attention. Thus, this research paper will discussed on the requirement of multimedia tutorial courseware especially in Islamic field and therefore, will come out with the prototsrpe on Islamic multimedia courseware. Base on the survey conducted, the demand of the courseware, the responds tov^ards this courseware development obtained from the educators and parents as a sample group to approve that this proj«;t is essential. The development of the prototype is base on to the children learning behavior and preferences since they are the target group for the courseware. Repetition technique from Cognitive Theories has been adapted to this prototype as well as gaming approach in order to incr^sing the understanding.